Digital promotion innovation of Ronggeng Ketuk Dance at Asem Gede Losarang Studio - Widi Eka Yulita; Tati Narawati; Fitri Kurniati (Himpunan Pengembang Kurikulum Indonesia (HIPKIN), 2024)
The advancement of digital technology has significantly impacted the promotion and presentation of Tari Ronggeng Ketuk. This study aims to describe how Sanggar Asem Gede Losarang utilizes digital technology to promote this dance. The main subject of the research is the owner of the sanggar, Dede Jaelani, while the object of the research is Tari Ronggeng Ketuk. This study is based on the grand theory of Cultural Studies, employing a qualitative paradigm with a multidisciplinary approach encompassing digital marketing and non-formal education (sanggar) and a descriptive analysis method. Data was collected using triangulation techniques, including interviews, observations, and document studies. The data analysis process in this research includes data reduction, presentation, and systematic verification to ensure data validity. The results indicate changes in the presentation of Tari Ronggeng Ketuk regarding the number of dancers, accompanying music, and performance duration due to the digital era. Promotion strategies include using the sanggar's blog, collaborating with influencers on social media platforms, partnering with photography communities, and participating in cultural activities such as Napak Jagat Pasundan. This research is expected to support the preservation of traditional dance and promote cultural heritage for the future. AbstrakPerkembangan teknologi digital telah memberikan dampak yang signifikan terhadap promosi dan penyajian Tari Ronggeng Ketuk. Penelitian ini bertujuan untuk mendeskripsikan bagaimana Sanggar Asem Gede Losarang memanfaatkan teknologi digital untuk mempromosikan tari ini. Subjek utama penelitian ini adalah Dede Jaelani, pemilik sanggar, sementara objek penelitiannya adalah Tari Ronggeng Ketuk. Penelitian ini berlandaskan pada grand theory Cultural Studies menggunakan paradigma kualitatif dengan pendekatan multidisiplin (pemasaran digital dan pendidikan non formal). Pengumpulan data dilakukan dengan menggunakan teknik triangulasi dengan proses analisis data meliputi reduksi, penyajian, dan verifikasi data secara sistematis untuk memastikan keabsahan data. Strategi promosi dalam penelitian ini dilakukan melalui tiga langkah: (1) perubahan konten yang disesuaikan untuk penampilan digital, (2) kerja sama dengan komunitas seni Napak Jagat Pasundan, dan (3) pemanfaatan media sosial seperti blog, Facebook, Instagram, dan YouTube sebagai sarana promosi. Strategi tersebut telah meningkatkan jumlah viewers tayangan Tari Ronggeng Ketuk sehingga leih dikenal oleh masyarakat luas. Penelitian ini diharapkan dapat mendukung pelestarian tari tradisional dan mempromosikan warisan budaya untuk masa depan.Kata Kunci: digital; promosi; studi budaya; tari ronggeng ketuk